Risk factors associated with gall bladder cancer in high incidence areas in India: a systematic review protocol - Melissa Glenda Lewis; Sandra Albert; Eliza K Dutta (BMJ Open)
Introduction Gall bladder cancer (GBC) is a lethal form of malignancy of the gastrointestinal tract with a unique geographical distribution. Cases are aggregated in the river basins of Ganga-Brahmaputra, in the north, east and north-east India, collectively termed as the ‘high-risk’ zone for GBC. Although some studies report high prevalence of typhoid infection linking with high burden of GBC in these regions, there is no systematic review of the factors associated with GBC in the high incidence areas. To address this gap, we are conducting a systematic review to identify and organise the factors associated with GBC in the high-risk zone of India.Methods and analysis A systematic review of all observational studies that report a quantitative relationship between at least one risk factor for GBC among adults (>18 years) in the high-risk zone in India will be conducted. The databases PubMed-MEDLINE, CINAHL, EMBASE, Web of Science, Scopus, OpenGrey and Google Scholar published in English and after 1990 will be searched. This review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. The primary outcome is GBC. If data permit, meta-analysis will be performed. Two independent reviewers will independently screen the articles, extract the data and assess the methodological quality of the studies.Ethics and dissemination As this will be a systematic review without human participants’ involvement, there will be no requirement for ethics approval. Findings will be disseminated widely through peer-reviewed publication and media, for example, conferences and symposia.PROSPERO registration number CRD42021256673.